Pemberdayaan Wanita Melalui Pengembangan Ekonomi Kreatif dan Digital Marketing di Desa Sojomerto - M Aryono Adhi; Rafael Surya Adi Pamungkas; Subhan Subhan (Universitas Negeri Semarang, 2026)
Community service “Women Empowerment through Creative Economy Development and Digital Marketing in Sojomerto Village” was carried out by the UNNES Giat 9 Team as part of the Semarang State University MBKM program. This activity aims to improve the understanding and skills of women's groups in Sojomerto Village about creative economy and digital marketing. The methods used include initial observation, socialization, mentoring and training in vegetable bouquet making, and evaluation. The results showed an increase in community awareness about the potential of the creative economy and the use of digital marketing to expand market share. The implementation of activities included making a vegetable bouquet that was exhibited at the Reban Expo, demonstrating the practical application of the knowledge gained. This service contributes to local economic development and women empowerment in Sojomerto Village.